2021
DOI: 10.1186/s12889-021-12303-5
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness as a mediator of social relationships and health-related quality of life among refugees living in North Rhine-Westphalia, Germany

Abstract: Background Since 2015, more than one million people fled to Germany – mainly from war-affected countries. Nevertheless, little is known about social determinants in refugees located in Germany. This study aims to test the mediation effect of loneliness between social relationships, comprising social integration and social support, and health-related quality of life among refugees living in North Rhine-Westphalia, Germany. Methods The investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…There might be an interaction between these areas such as that a negative self-concept increases the risk of social withdrawal and in turn a lack of positive relational experiences reinforces the negative self-concept . Overall, refugees have a higher risk of loneliness and low social support, factors that have been repeatedly related to higher levels of mental distress [ 62 ], CPTSD [ 63 ] and lower quality of life [ 64 ]. Additionally, we suggest that numbness due to affective dysregulation and an associated reduced self-awareness or ability to engage in interpersonal relationships might further promote disturbances in relationships and a negative self-concept .…”
Section: Discussionmentioning
confidence: 99%
“…There might be an interaction between these areas such as that a negative self-concept increases the risk of social withdrawal and in turn a lack of positive relational experiences reinforces the negative self-concept . Overall, refugees have a higher risk of loneliness and low social support, factors that have been repeatedly related to higher levels of mental distress [ 62 ], CPTSD [ 63 ] and lower quality of life [ 64 ]. Additionally, we suggest that numbness due to affective dysregulation and an associated reduced self-awareness or ability to engage in interpersonal relationships might further promote disturbances in relationships and a negative self-concept .…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been identified as one of the most important risk factors for PTSD in non-refugee traumatized groups [90], but more studies in the present review reported its correlation with PGD. In individualistic host societies, refugees often experience loneliness, which has negative effects on health [95,96]. When the deceased was the major source of social support, building new relationships of trust and support may be especially difficult in a post-migration setting.…”
Section: Associated Factorsmentioning
confidence: 99%
“…Although social support has been identified as one of the most important risk factors for PTSD in non-refugee traumatized samples (79), more studies in the present review reported its correlation with PGD. In individualistic host societies, refugees often experience great loneliness which has negative effects on health (94,95). When the deceased was the major source of social support, building new relationships of trust and support may be especially difficult in a post-migration setting.…”
Section: Associated Factorsmentioning
confidence: 99%